2019
DOI: 10.1088/2040-8986/ab0d5f
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally tunable polarization-insensitive single and multifocal metasurface

Abstract: Metasurfaces with superior capabilities to tailor wave fronts of light have become one of the most widely investigated optical elements. Incorporating tunable features into the metasurface design is required. In this study, we have proposed and designed highly efficient rotationally tunable metasurface lens structures inspired by Moiré lenses operating at a 532 nm wavelength. The proposed structures consist of two cascaded all-dielectric metasurfaces, which have reverse phase profiles with respect to each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Furthermore, rotation of a metalenses doublet can tune its focal length. [107][108][109][110] Mutual rotation of doublet metalenses has been shown to tune the focal length using Moiré metalenses that are axially asymmetric doublet lens 97 [Fig. 3(c)].…”
Section: Tunable Metalenses By Non-electrical Inputmentioning
confidence: 99%
“…Furthermore, rotation of a metalenses doublet can tune its focal length. [107][108][109][110] Mutual rotation of doublet metalenses has been shown to tune the focal length using Moiré metalenses that are axially asymmetric doublet lens 97 [Fig. 3(c)].…”
Section: Tunable Metalenses By Non-electrical Inputmentioning
confidence: 99%
“…[ 151 ] proposed a rotationally tunable polarization‐dependent varifocal metasurface, and Yilmaz et al. [ 152 ] demonstrated a polarization‐independent varifocal metasurface. Subsequently, Guo et al.…”
Section: Functionalitiesmentioning
confidence: 99%
“…[ 147,148 ] A derivative of the Alvarez system is also presented where the two lenses are coaxially rotated rather than being parallelly moved, which is inspired by the Moiré lens. [ 149–153 ] Cui et al. [ 151 ] proposed a rotationally tunable polarization‐dependent varifocal metasurface, and Yilmaz et al.…”
Section: Functionalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers combine the zooming method in traditional optics with metalens. For example, Ehsan Arbabi et al demonstrated tunable metasurface doublets based on micro-electromechanical systems [ 6 , 7 ], Nazmi Yilmaz et al proposed highly efficient rotationally tunable metasurface lens structures inspired by Moiré lenses [ 8 , 9 ] and Shane Colburn et al built a 1 cm aperture varifocal metalens system at 1550 nm wavelength inspired by an Alvarez lens [ 10 ]. Some researchers used unique optical modulation methods in the metasurfaces to realize the step zoom lens.…”
Section: Introductionmentioning
confidence: 99%